2022
DOI: 10.1134/s036176882208014x
|View full text |Cite
|
Sign up to set email alerts
|

Towards Conversational Agents to support Informal Caregivers of People with Dementia: Challenges and Opportunities

Abstract: People who have dementia (PwD) experience deteriorating executive functions, in particular their working memory, and therefore find it hard to complete multistep tasks or activities of daily living. There is no doubt that during the pandemic, PwD and their caregivers were particularly vulnerable, often isolated which affected their mental and physical health. Their ability to live independently was hampered, fomenting depression in the PwD and burnout on informal caregivers. Information technology can support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…User-Centered Design (UCD) is a design methodology focused on the needs of users to develop products and services by improving usability, accessibility and user experience, which translates into greater user satisfaction in the use of the product or service. According to Norman and Draper [14], the (DCU) identifies the needs, requirements and limitations of users to design products that meet those needs effectively and efficiently, to achieve this the design process must be iterative and collaborative, with the active participation of users and designers in all stages of the process, for example , conversational agents for informal caregivers , applying a descriptive phenomenological qualitative study to carry out a questionnaire of open questions for the care of people with dementia and piloted with a commercial device [15] and the automatic translate service of the Nahuatl language , on topics of inclusion when Nahuatl spoken in regions where English the dominant language . This leads native people to in some way forget their mother language in favor of Spanish.…”
Section: Methodsmentioning
confidence: 99%
“…User-Centered Design (UCD) is a design methodology focused on the needs of users to develop products and services by improving usability, accessibility and user experience, which translates into greater user satisfaction in the use of the product or service. According to Norman and Draper [14], the (DCU) identifies the needs, requirements and limitations of users to design products that meet those needs effectively and efficiently, to achieve this the design process must be iterative and collaborative, with the active participation of users and designers in all stages of the process, for example , conversational agents for informal caregivers , applying a descriptive phenomenological qualitative study to carry out a questionnaire of open questions for the care of people with dementia and piloted with a commercial device [15] and the automatic translate service of the Nahuatl language , on topics of inclusion when Nahuatl spoken in regions where English the dominant language . This leads native people to in some way forget their mother language in favor of Spanish.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a recent study discussed the unique challenges and opportunities of conversational agents to support dementia caregivers (Jiménez, et al, 2022). The authors conducted a qualitative study with 7 participants who identified forgetting things and repetitive questioning as the most challenging behaviours of the PWD, factors that have not yet been tackled with a conversational agent.…”
Section: Conversational Agents For Caregiversmentioning
confidence: 99%
“…The first phase of the study involved semi-structured interviews with dementia caregivers and experts in dementia. The purpose was to inform the design of our chatbot (Jiménez, et al, 2022). Our findings were transformed into chatbot design, system design, and conversational design requirements.…”
Section: Stakeholder Engagementmentioning
confidence: 99%